The Effect of Capital Expenditure and Gross Fixed Capital Formation on Income Disparity in West Coast Region of North Sumatera. (May 2019) - Purba, B; Masbar, R; Maipita, I; Jamal, A
Abstract: This study purposes to determine the effect of capital expenditure and gross fixed capital formation on income disparity among districts/cities in West Coast Region in North Sumatera-Indonesia. Analysis of economic development disparity was calculated by Williamson's Index. The research method was carried out using panel data regression. The result of this research that used annual data for 2012-2016 are: (1) the average of disparity in economic development included in the extremely low category, (2) the capital expenditure variable and gross fixed capital formation variable have significant positive effects on income disparity of the West Coast Region of North Sumatera.